HIV Rapid Testing in the General Population and the Usefulness of PrEP in Ecuador: A Cost–Utility Analysis - Quirola-Amores, Paulina; Espinosa, Pablo; Oleas, Sebastian; Hernandez, Isabel; Henriquez, Aquiles R.; Teran, Enrique (Frontiers in Public Health, 2022)
Introduction HIV is considered one of the most important chronic transmitted diseases worldwide. The Joint United Nations Program on HIV/AIDS in 2020 proposed the strategy “95–95–95” which goals to achieve a 95% of cases identified, receives ART, and will have achieved suppression of the virus. In Ecuador by 2020, according to the Ministry of Public Health, 45,056 persons are living with HIV, principally men between 15 and 49 years, and a mortality rate of 4.8/100,000 habitats. This study aims to determine the cost–utility of applying an early screening to a sexually active population vs. only a high-risk population and if the use of PrEP is justified depending on different contexts. Methods For the cost–utility evaluation, it was compared: (a) HIV screening performed only in the high-risk population vs. HIV screening in all population sexually active; and (b) the use of ART only for HIV treatment vs. ART as a treatment in diagnosed cases and the use of PrEP (only at a high-risk population of acquiring HIV). Calculation and weight of DALYs for HIV/SIDA were obtained through WHO guidelines. To generate the Markov model for HIV/AIDS, subjects were classified as symptomatic or asymptomatic, as well as the HIV deaths. Results Cost–benefit analysis (CUA) showed that ICER for early diagnosis had a negative value which means a saving if the strategy will be implemented as a regular test (–$591, –$4,360) and −108 and −934 DALYs, in the case of ART and PrEP, ICER the $30,541–$59,410, which resulted in more than the GDP's threshold and health years between 2,511 and 10,635 in the general population. With a reduction of 70% in the assigned budget for the early diagnosis, Ecuadorian people could lose between 4 and 6 DALYs, while if the budget reduces more than 50% to ART, it will generate a loss of 10–12 years of healthy life. Conclusion CUA demonstrates that an early diagnosis in a sexually active population is cost-beneficial. This, combined with ART or PrEP, is ideal to add years of healthy life.